ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI DALAM NEGERI DI PROPINSI JAWA TENGAH - Sindhu Rakasiwi, Sri Wahyuning , (STEKOM, 2014)
Domestic Investment in Central Java for years to come still expect any contributing factors that can accelerate the realization of the investment, because in fact the realization of investment to domestic investment in Central Java is still less rapidly than other provinces on the island of Java such as Jakarta, West Java and East Java. This is due to lack of infrastructure and facilities that are less supportive. On that basis then in this study will be conducted an analysis of the factors that influence the Domestic Investment in Central Java. The research goal to analyze the influence of Gross Regional Domestic Product, labor force, inflation and Infrastructure on Domestic Investment (PMDN) in Central Java Province, the period of 2005-2009. Study sample as many as 33 districts / cities in Central Java Province, where the method used was purposive sampling, with the criteria is the district / city in Central Java who have realized investment in 2005 until 2009. Analysis tool used is descriptive statistical tests, assumptions of classical, linear regression, t test, F test and coefficient of determination. The results of this study concluded that the first hypothesis which states that GDP significant effect on domestic investment, accepted. The second hypothesis that the workforce have a significant effect on domestic investment, accepted. The third hypothesis that inflation significantly affect domestic investment, can not be accepted (rejected), and the fourth hypothesis which states that the length of road infrastructure in the form of significant effect on domestic investment, accepted. Key words : domestic investment, GDP, labor force, inflation, long way, multiple regression